Pemodelan Sistem Pertanian Terintegrasi Pendekatan: Programasi Linier - NP. SUKANTERI; M. NARKA TENAYA; IW. BUDIASA (Universitas Udayana, 2013)
This study aims at finding an optimal model of integrated farming systems development (henceforth Simantri) on implementing Simantri 079 farmer groups based on existing farming constraints and available technology. Primary data were collected from 20 respondents by applying survey methods with census techniques in Simantri 079 farmer groups in Tabanan regency. Secondary data were obtained from various sources to specify all the parameters used in the model. Data were analyzed by using gross margin and a linear programming (BLPX88 package program). Linear programing aimed at selecting combination and levels of activities in order to achieve the goal without compromising to the availability of resources and specified constraints. The use of gross margin aims at determining the farming income under the simantri 079. The results showed that the average of farm size is about 0,33 hectars. Those area are utilized to grow rice twice a year and corn once a year with cropping pattern : paddy- paddy-second crop. Land for cattle obtained from a member of Simantri group is about 0.1 hectares. Actual income of farmers per hectare got from the operation of the Simantri equal to Rp 15,239,000.00 from the first rice production, Rp 20,896,000.00 from the second rice production and Rp 3,678.000,00 from corn production in the last session. Income of cattle production per year is Rp 3,819,000.00. Under the optimization overall farmer income at amount of Rp335,562,600.00 on 6,61 hectars and 20 cattles a year. But the real income Rp 332,026,141,45.00 making a different of 1.07% above from real income.